A PRESPECTIVE STUDY ON APOBEC PROTEIN FAMILY - GEJALAKSHMI, S.; HARIKRISHNAN, N.; KOMAL, S. (International Journal of Current Pharmaceutical Research, 2019)
Apobec is an apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like" is a family of deaminases. It has two types of APOBEC enzymes n-terminal of apobec enzyme and C-terminal of APOBEC enzyme. N-terminal domain is catalytic domain and C-terminal domain is a pseudo catalytic domain. Pathogen and cellular genome undergo mutation by human DNA cytosine to uracil deaminases. Three subtypes of APOBEC3D. APOBEC3F, APOBEC3G and APOBEC3H restrict human deficiency virus-1. Two APOBEC enzymes are the sources of somatic mutagenesis in cancer cells that drive tumor evolution and manifest clinically as theraphy resistance. This review of the APOBEC family will focus on an open question in regulation, namely what role the interactions of these proteins with RNA have in editing substrate recognition or allosteric regulation of DNA mutagenic and host-defense activities.